The way out of drug addiction - Boučková, Monika (Univerzita Pardubice, 2023)
The work deals with the integration of drug users back into society. On the way from a user habit to an abstinent habit. What complications are involved in this transition, and how the given rituals change during it. It intertwines the testimony of users and abstainers, which are accompanied by the testimony of an addictologist and a social worker of a support organization for drug users. The process of refusing drugs and starting abstinence is also mentioned, and will focus on the main reasons and follow-up procedures. The diploma thesis is based on the theoretical concepts Habitus by Pierre Bourdieu and Ritual by Victor Turner and Arnold van Gannep. The text is accompanied by audiovisual processing.
Cesta z drogové závislosti
Keywords: drogy; závislost; abstinence; budoucnost; motivace; drugs; addiction; abstinence; future; motivation